Pengembangan Bank Sampahsebagai Solusi Pengelolaan Sampah Berkelanjutan di Desa Jl Sosro GG 1001 - Nabila Ardini; Riyan Pradesyah (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Effective waste management is a crucial challenge in maintaining environmental cleanliness and sustainability, especially in rural areas. This study aims to analyze the development of waste banks as a sustainable waste management solution in Jl Sosro GG 1001 Village. The research method used is qualitative descriptive with data collection techniques through field observations, in-depth interviews with residents and waste bank managers, and documentation of activities. The results of the study show that the existence of waste banks is able to increase public awareness in sorting and managing household waste. In addition, the social and economic impacts caused are quite significant, such as the formation of work groups, increased additional income, and strengthening the value of mutual cooperation. However, there are a number of challenges that hinder program optimization, including limited operational facilities, lack of continuity of community participation, and lack of technical support from local governments. To overcome this, a capacity building strategy is needed through continuous training, provision of supporting facilities, and cross-sector collaboration. The waste bank in Jl Sosro GG 1001 Village has great potential to be used as a model of sustainable community-based waste management, if supported by a joint commitment between residents, the government, and other stakeholders.